Twórcza destrukcja jako uwarunkowanie efektywności przedsiębiorstwa - Osbert-Pociecha, Grażyna (The Creative Destruction as a Condition of Efficiency, 2005)
According to last results of research - the creative destruction is a very important factor of firm's success. Simultaneously it was confirmed that the market make the creative destruction more efficiently then individual firms. So if company which want to be competitive, must make an effort to both concentrate and learn of the creative destruction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 332-342